SMOKING PLAYING AS A RISK FACTOR TO OTHER DISEASES: A META-ANALYSIS (Journal of Pharmaceutical Negative Results, 2023)
On July 21, 2021, a report from the World Health Organization indicated that there are presently 1.3 billion tobacco smokers globally. Data statistics show that the mortality rate of tobacco use is already at 3,021,098. Although smoking receives the lowest mortality rate among other communicable and non-communicable diseases in 2021, research suggests that smoking could hamper the quality of life of someone who already has an existing illness. This study investigated the adverse effects of smoking as a contributory factor to communicable diseases such as HIV/AIDS, Tuberculosis, and COVID-19, non-communicable diseases like Malaria and Dengue, and risk factors such as alcohol and obesity. The locale of the study is Philippines. Meta-analysis is utilized in order to examine data statistics of the Philippines in comparison to its Southeast Asian neighbors. Meta- analysis was used by the author to extrapolate data from various quantitative and qualitative documents from 2000 up to the present. Specifically, open-access journal articles and data from legitimate databases like ISI Scopus-indexed journals and/or websites were collated substantially.